Pengaruh Earning Per Share dan World Gold Price Terhadap Harga Saham pada PT Aneka Tambang Tbk Periode 2013 - 2022 - Dina Adillah Yanuarta; Siti Nurcahayati (STIE AUB Surakarta, 2025)
This study aims to examine the effect of Earning Per Share and World Gold Price on the Stock Price of PT Aneka Tambang Tbk during the 2013-2022 period. The research employs a quantitative descriptive approach. The population consists of financial reports, using income statements and notes to financial statements selected as the sample. The analytical methods include classical assumption testing, multiple linier regression analysis, hypothesis testing, and the coefficient of determination. The t-test results indicate that Earning Per Share has a significance value of 0.625 (> 0.05) and a t-count of 0.511 (< 2.36462), showing that EPS has no significant partial effect on stock prices. Meanwhile, World Gold Price demonstrates a significant partial effect with a significance value of 0.046 (< 0.05) and a t-count of 2.416 (> 2.36462). The F-test yields an F-count of 9.959 (> 4.74) with a significance level of 0.008 (< 0.05), implying that Earning Per Share and World Gold Price jointly have a significant effect on stock prices. The adjusted R-square value of 0.666 indicates that 66.6% of the variation in stock prices is influenced by Earning Per Share and World Gold Price, while the remaining 33.4% is affected by other factors not examined in this study.